2011
DOI: 10.2337/db10-1628
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk Between Interferon-γ and Hedgehog Signaling Regulates Adipogenesis

Abstract: OBJECTIVET cells and level of the cytokine interferon-γ (IFN-γ) are increased in adipose tissue in obesity. Hedgehog (Hh) signaling has been shown to potently inhibit white adipocyte differentiation. In light of recent findings in neurons that IFN-γ and Hh signaling cross-talk, we examined their potential interaction in the context of adipogenesis.RESEARCH DESIGN AND METHODSWe used Hh reporter cells, cell lines, and primary adipocyte differentiation models to explore costimulation of IFN-γ and Hh signaling. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…The finding is in keeping with recent studies showing that IFN␥ promotes adipogenesis and adipocyte differentiation via inhibition of hedgehog signaling (27). Adipocytes were overall more abundant in the thyroid of IFN␥ transgenic mice than in those of wild-type controls but were markedly influenced by the genetic background.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding is in keeping with recent studies showing that IFN␥ promotes adipogenesis and adipocyte differentiation via inhibition of hedgehog signaling (27). Adipocytes were overall more abundant in the thyroid of IFN␥ transgenic mice than in those of wild-type controls but were markedly influenced by the genetic background.…”
Section: Discussionsupporting
confidence: 90%
“…This explanation seems unlikely, however, because adipocytes were found also in IFN␥ transgenic that had mild thyroid disruption. We favor a scenario in which adipocytes are recruited to the thyroid as a direct consequence of IFN␥, in keeping with the stimulatory role IFN␥ has on adipogenesis (27). Recent studies have highlighted a crosstalk between adipocytes and macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…IFN-γ) may be regarded as a mechanism contributing to inflammation in obesity. Todoric et al [2] proposed a possible mechanism by which IFN-γ may be involved in the pathogenesis of obesity. They demonstrated that IFN-γ is a potent inhibitor of Hedgehog signaling: a inhibitor in white adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanisms of how these changes lead to the accumulation of fat mass are not yet fully understood. Recent studies have shown that inflammation also has a role in the pathogenesis of obesity [2]. Different inflammatory markers, such as IL-6, IL-1β, CRP, and TNF-α, are increased in childhood obesity [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Shh signaling specifically blocks adipogenesis in white, but not brown adipose tissue [69,92]. IFNγ inhibits fat cell differentiation in the absence of Shh signaling [30,40,96]. However, when the Shh pathway is activated in various preadipocyte model systems, IFNγ blocks Shh signaling and rescues adipogenesis via a JAK-STAT1-dependent mechanism [96].…”
Section: Regulation Of Adipogenesis By Stat Proteinsmentioning
confidence: 99%